Groups : process and practice - Corey, Marianne Schneider, 1942-; Corey, Gerald; Corey, Cindy (Cindy C.); Brooks/Cole Publishing Company (Belmont, Calif. : Brooks/Cole)
Includes bibliographical references (p. 431-443) and index